Analisis Konseptual Fungsi Legislasi BPD dalam Pembentukan Peraturan Desa Berdasarkan UU Desa - Haliza Fatimah (Public Service and Governance Journal, 2025)
This study aims to conceptually analyze the legislative function of the Village Consultative Body (BPD) in the formation of Village Regulations based on the Village Law as stipulated in Law Number 3 of 2024, as well as to identify the challenges in its implementation. This research employs a literature study method with a qualitative approach through the review of relevant sources, including academic journals, books, and policy documents. The findings indicate that the implementation of BPD’s legislative function still faces several obstacles, such as limited human resource capacity, a lack of understanding of legal aspects, the absence of systematic legislative planning, and weak coordination between the BPD and the Village Head. The implications of this study reveal that the legislative function of the BPD has not been optimally implemented. This underscores the need for institutional capacity strengthening, improved synergy among village-level stakeholders, the formulation of a Village Legislative Program (Prolegdes), technical facilitation by local governments, and adequate support for operational funding.